Dancing in the movies - Boswell, Robert, 1953- (Iowa School of Letters award for short fiction., 1986)
Encompassing a vast gamut of personalities, situations, and emotions, these stories penetrate our motives for doing what is right. Often there is no right or wrong, and the characters' motives for the choices they make are as diverse as the childhood memories they cherish and abhor. In the end, this book probes individual impulse and responsibility, creating stories so unerringly authentic that they become irrepressibly part of everyone who reads them.